Serum biomarkers of fibrosis and extracellular matrix remodeling in patients with nonalcoholic fatty liver disease: association with liver histology - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2019)
Background We sought to explore the interplay of multiple serum biomarkers of fibrosis and extracellular matrix remodeling with the results of liver histology in patients with nonalcoholic fatty liver disease (NAFLD). Patients and methods Venous blood samples were collected from 80 patients with biopsy-proven NAFLD and 59 age-matched and sex-matched healthy controls. Serum levels of transforming growth factor (TGF)-beta 1, TGF-beta 2, matrix metalloproteinases (MMP)-1, MMP-2, MMP-7, MMP-9, MMP-10, tissue inhibitors of metalloproteinase (TIMP)-1, and TIMP-2 were determined by using the Luminex MagPix technology on a MAGPIX analyzer. Results We documented significant differences in the levels of TGF-beta 1, TGF-beta 2, MMP-2, MMP-7, MMP-9, TIMP-1, and TIMP-2 between NAFLD patients and controls. However, none of these biomarkers was able to distinguish between nonalcoholic steatohepatitis and nonalcoholic fatty liver. TIMP-1 levels were significantly higher in patients with significant fibrosis (fibrosis stage >= 2; 2624 +/- 1261 pg/ml) than in those without (fibrosis stage 0-1; 2096 +/- 906 pg/ml; P=0.03). Moreover, serum levels of TIMP-1 were identified as the only independent predictor of histological fibrosis (beta=0.298, t=2.7, P=0.007). Conclusion Our study provides insights into the association of multiple serum biomarkers of fibrosis and extracellular matrix remodeling with NAFLD histology. Notably, serum levels of TIMP-1 were identified as a clinically useful marker for distinguishing NAFLD patients with and without significant fibrosis. Copyright (c) 2018 Wolters Kluwer Health, Inc. All rights reserved.
Keywords: biomarkers; extracellular matrix; fibrosis; multiplex technology; nonalcoholic fatty liver disease; nonalcoholic steatohepatitis; STEATOHEPATITIS NASH; TISSUE INHIBITORS; SCORING SYSTEM; METALLOPROTEINASES; HISTOPATHOLOGY; CARCINOGENESIS; UTILITY